Mobile veterinary service: an alternative business model. Issue 8 (1st September 2016) - Forster, Daniel; Forster, Kirsty
Abstract : Daniel and Kirsty Forster recently won a Queen's Award for Innovation for a mobile veterinary service on the Isle of Wight. Here they describe what led them to set up the service along with what was involved.